Argyrodite type solid electrolyte as well as preparation method and application thereof

By doping Mg, Ti, F to LPSCl, a sulfur-silver germanium ore-type solid electrolyte with higher ionic conductivity and wet stability was prepared, which solved the problems of low conductivity and sensitivity to water and oxygen at room temperature, and achieved more stable electrochemical performance.

CN119695254AActive Publication Date: 2025-03-25DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311236576.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-22
Publication Date
2025-03-25
Estimated Expiration
2043-09-22

AI Technical Summary

Technical Problem

The existing sulfur-silver germanium ore solid electrolyte has low ionic conductivity at room temperature, is sensitive to water and oxygen, and has poor interface compatibility, which affects its application in all-solid lithium-ion batteries.

Method used

Through planetary grinding and solid phase sintering, Mg, Ti, F doped LPSCl (lithium phosphorus thiochloride) sulfur silver germanium ore-type solid electrolyte is prepared to improve its air stability and stability to metal lithium.

Benefits of technology

It improves the ionic conductivity and wet stability of sulfur-silver germanium ore solid electrolyte, enhances the stability with lithium metal, and meets the application needs of all-solid lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695254A_ABST
    Figure CN119695254A_ABST
Patent Text Reader

Abstract

The invention discloses argyrodite type solid electrolyte as well as a preparation method and application thereof, and belongs to the field of solid-state batteries. The argyrodite type sulfide solid electrolyte with excellent wet stability is obtained mainly by carrying out Mg, Ti and F doping modification on the sulfide solid electrolyte LPSCl (lithium phosphorus sulfur chloride), and the lithium metal symmetric battery is designed and assembled, so that the electrolyte has excellent electrochemical performance. The chemical formula of the sulfide solid electrolyte is Li < 5.4 + 5x > P < 1-2x > (Mg-Ti) < x > S < 4.4 > Cl < 1.6-5x > F < 5x >, xlt; and 0.3. The preparation method of the argyrodite type solid electrolyte is simple and effective, and meanwhile, the argyrodite type solid electrolyte has relatively good cycling stability on metal lithium, and is expected to solve the practical application problem of a sulfide solid electrolyte as an all-solid-state lithium ion battery electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a argyrodite-type solid electrolyte, belonging to the technical field of sulfide solid-state batteries. Background Art

[0002] Advanced battery technology is the key supporting technology for achieving carbon peak and carbon neutrality. With the rapid growth of market demand for portable electronic products, energy storage products and power batteries. All-solid-state lithium-ion batteries use solid electrolytes instead of flammable liquid organic electrolytes, which is expected to fundamentally solve the safety problem of batteries. In addition, since solid electrolytes can match high-voltage positive electrodes and high-capacity, low-potential metal lithium negative electrodes, all-solid-state lithium batteries can achieve higher energy density. Therefore, all-solid-state lithium-ion batteries are expected to become the next generation of high-energy-density batteries. At present, the existing solid electrolytes are mainly divided into three types: oxide solid electrolytes, polymer solid electrolytes and sulfide solid electrolytes. Sulfide solid electrolytes are considered to be the most promising solid electrolyte materials for industrialization because of their high ionic conductivity, wide electrochemical window and good processing performance. The room temperature ionic conductivity of common argyrodite-type sulfide solid electrolytes is generally around 10mS / cm, which is comparable to liquid organic electrolytes. However, due to its sensitivity to water and oxygen, poor interfacial compatibility with lithium-ion battery cathode materials, and poor stability to lithium metal on the negative electrode side, the practical application of argyrodite-type solid electrolytes is limited. Therefore, it is urgent to find low-cost and better-performing sulfide solid electrolytes and apply them to all-solid-state lithium-ion batteries. Summary of the invention

[0003] According to one aspect of the present application, a argyrodite-type solid electrolyte is provided, and a Mg-, Ti-, and F-doped LPSCl (lithium phosphorus sulfur chloride) argyrodite-type solid electrolyte is prepared by planetary ball milling and solid-phase sintering, and an all-solid-state battery is assembled, thereby improving the air stability and stability of the electrolyte to metallic lithium and promoting its commercial development.

[0004] This application adopts the following technical solutions:

[0005] A argyrodite-type solid electrolyte, wherein the chemical formula of the argyrodite-type solid electrolyte is Li 5.4+5x P 1-2x (Mg-Ti) x S 4.4 Cl 1.6-5x F 5x ;

[0006] Among them, 0 <x<0.3。

[0007] Optionally, 0.05 <x<0.2。

[0008] Optionally, x is selected from any value among 0.05, 0.1, 0.12, 0.15, 0.16, 0.2, or any range therebetween.

[0009] Optionally, the ionic conductivity of the argyrodite-type solid electrolyte at 20 to 30° C. is 1 to 4 mS / cm.

[0010] The ionic conductivity of the argyrodite-type solid electrolyte of the present application at room temperature is 1 to 4 mS / cm, which meets the application requirements of all-solid-state lithium-ion batteries.

[0011] According to another aspect of the present application, a method for preparing the above-mentioned argyrodite-type solid electrolyte is also provided, comprising the following steps:

[0012] The mixed raw materials containing Li2S, P2S5, MgF2, TiF3 and LiCl are ball-milled, roasted and sintered to obtain the argyrodite-type solid electrolyte.

[0013] Optionally, in the mixed raw material, the molar ratio of Li2S, P2S5, MgF2, TiF3 and LiCl is calculated based on the molar ratio of each element in the chemical formula of claim 1.

[0014] Optionally, in the mixed raw material, the molar ratio of Li2S, P2S5, MgF2, TiF3 and LiCl is (1.9+5x):(0.5-x):x:x:(1.65-5x);

[0015] Among them, 0 <x<0.3。

[0016] Optionally, the mixed raw material contains 2.03 to 2.80 parts by mass of Li2S, 0.29 to 0.43 parts by mass of P2S5, 0.05 to 0.19 parts by mass of MgF2, 0.05 to 0.19 parts by mass of TiF3, and 0.58 to 1.28 parts by mass of LiCl.

[0017] Optionally, the ball milling conditions include: a rotation speed of 100 to 500 r / min, and a ball milling time of 45 to 1200 min.

[0018] Optionally, the ball milling conditions include: a rotation speed of 300 to 500 r / min.

[0019] Optionally, the ball milling conditions include: a rotation speed selected from any value of 100 r / min, 200 r / min, 300 r / min, 400 r / min, 500 r / min, or any range between the two.

[0020] Optionally, the ball milling conditions include: the ball milling time is 600 to 1140 minutes.

[0021] Optionally, the ball milling conditions include: the ball milling time is selected from any value of 600 min, 700 min, 800 min, 900 min, 1000 min, 1100 min, 1140 min or any range between two of them.

[0022] Optionally, a pre-grinding step is also included before the ball milling.

[0023] Optionally, the pre-grinding conditions include: a rotation speed of 100 to 300 r / min, and a pre-grinding time of 60 to 120 min.

[0024] Optionally, the rotation speed of the pre-grinding is selected from any value among 100r / min, 200r / min, 300r / min or any range between the two.

[0025] Optionally, the pre-grinding time is selected from any value among 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min, or any range between two of them.

[0026] Optionally, the calcination conditions include: a temperature of 400 to 500° C. and a calcination time of 8 to 12 hours.

[0027] Optionally, the calcination time is selected from any value among 8h, 9h, 10h, 11h, 12h, or any range between two of them.

[0028] Optionally, the step of tableting is further included after the calcination;

[0029] The tabletting conditions include: a pressure of 10 to 15 MPa.

[0030] Optionally, the tabletting pressure is selected from any value among 10 MPa, 11 MPa, 12 MPa, 13 MPa, 14 MPa, 15 MPa, or any range between two values.

[0031] After ball milling, an amorphous phase mixture of sulfide solid electrolyte is obtained, and cold pressing is performed to obtain a green embryo.

[0032] Optionally, the sintering conditions include: the sintering atmosphere is an inert gas atmosphere, the sintering heating rate is 5 to 10° C. / min, the sintering temperature is 200 to 475° C., and the sintering time is 6 to 12 hours.

[0033] Optionally, the sintering temperature is selected from any value of 200° C., 250° C., 300° C., 350° C., 400° C., 475° C., or any range therebetween.

[0034] Optionally, the sintering time is selected from any value among 6h, 7h, 8h, 9h, 10h, 11h, 12h, or any range between two of them.

[0035] Optionally, the heating rate of sintering is selected from any value of 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, or any range therebetween.

[0036] Optionally, the inert gas atmosphere is selected from at least one of nitrogen, helium and argon.

[0037] Optionally, the sintering further includes a grinding step into powder.

[0038] According to another aspect of the present application, there is also provided an application of at least one of the above-mentioned argyrodite-type solid electrolyte and the argyrodite-type solid electrolyte prepared according to the above-mentioned preparation method as an electrolyte for an all-solid-state lithium-ion battery.

[0039] Optionally, the argyrodite-type solid electrolyte is Li 5.65 P 0.90 (Mg-Ti) 0.05 S 4.4 Cl 1.35 F 0.25 , Li 5.9 P 0.8 (Mg-Ti) 0.1 S 4.4 Cl 1.1 F 0.5 , Li6P 0.75 (Mg-Ti) 0.12 S 4.4 CIF 0.6 , Li 6.15 P 0.7 (Mg-Ti) 0.15 S 4.4 Cl 0.85 F 0.75 , Li 6.2 P 0.68 (Mg-Ti) 0.16 S 4.4 Cl 0.8 F 0.8 , Li 6.4 P 0.6 (Mg-Ti) 0.2 S 4.4 Cl 0.6 F 1.0 At least one of .

[0040] The negative electrode uses cut Li foil.

[0041] The present application discloses a argyrodite-type solid electrolyte and its preparation method and application. This application belongs to the field of solid-state batteries. The present application mainly obtains a argyrodite-type sulfide solid electrolyte with excellent wet stability by doping Mg, Ti, and F on the sulfide solid electrolyte LPSCl (lithium phosphorus sulfur chloride). By designing and assembling a lithium metal symmetric battery, it is shown that the electrolyte has excellent electrochemical properties.

[0042] The beneficial effects of this application include:

[0043] The argyrodite structure of the argyrodite-type solid electrolyte provided in this application effectively shortens the Li + The transmission path is shortened, which reduces the grain boundary limitation and ensures that the sulfide solid electrolyte has a suitable ionic conductivity; LiCl and LiF can form a protective layer during the charge and discharge process, effectively inhibiting the growth of dendrites; Mg and Ti doping replace the P site of argyrodite-type electrolyte, which can significantly improve the air stability of the electrolyte and is expected to realize high-voltage all-solid-state lithium-ion batteries, further improving the energy density and cycle life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 The argyrodite-type solid electrolyte sheet and solid electrolyte LPSCl of Examples 1 to 6 of the present application 1.6 Photographs taken after the slides were immersed in water for 1 minute.

[0045] Figure 2 It is an X-ray diffraction diagram of the argyrodite-type solid electrolyte of the embodiment of the present application.

[0046] Figure 3 Li is used in Example 1 of this application 6.4 P 0.6 (Mg-Ti) 0.2 S 4.4 Cl 0.6 F 1.0 Constant current charge and discharge test curves of metallic lithium symmetric batteries assembled as electrolyte.

[0047] Figure 4 Li is used in Example 1 of this application 6.4 P 0.6 (Mg-Ti) 0.2 S 4.4 Cl 0.6 F 1.0 Scanning electron microscope image and energy spectrum of a symmetric lithium metal battery assembled as electrolyte after constant current charge and discharge test. DETAILED DESCRIPTION

[0048] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0049] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0050] According to one implementation of the present application:

[0051] LiCl, MgF2, TiF3, Li2S, P2S5 with a molar ratio of 0.7-1.53: 0.06-0.23: 0.06-0.23: 2.44-3.36: 0.51-1.13 are placed in a ball mill, pre-milled at 100-300 rpm for 1-2 hours, and ball milled at 300-500 rpm for 10-20 hours to obtain an amorphous phase mixture of sulfide solid electrolyte, which is cold-pressed to obtain a blank, placed in a quartz tube, and heated to 400-500° C. for 8-12 hours at room temperature. The temperature is lowered to room temperature to obtain a ceramic phase argyrodite-type solid electrolyte, which is then taken out of the ball mill for use.

[0052] The ball-milled amorphous mixture is pressed into a tablet at a pressure of 10MPa to 15MPa and a tablet diameter of 10cm to 13cm. The temperature is then raised to 200 to 475°C at a rate of 5 to 10°C / min under Ar gas protection, kept for 6 to 12 hours, and naturally cooled to room temperature. The sintered electrolyte is then ground into powder for later use.

[0053] The argyrodite-type solid electrolyte is placed in a solid-state battery mold, and the interface is kept in close contact by a pressure of 200 to 500 MPa. The cut Li foils are placed on both sides to assemble a metallic lithium symmetric battery, and finally its electrochemical performance is tested.

[0054] Example 1

[0055] LiCl, Li2S, P2S5, MgF2, and TiF3 with a molar ratio of 0.58:2.80:0.29:0.19:0.19 were placed in a ball mill, and pre-milled at 100 rpm for 1h, ball milled at 300 rpm for 2h, and ball milled at 500 rpm for 20h to obtain an amorphous phase mixture of argyrodite-type solid electrolyte. The blank was cold-pressed to obtain a blank, placed in a quartz tube, and heated to 500°C for 12h at room temperature. The temperature was lowered to room temperature to obtain a ceramic phase sulfide solid electrolyte Li 6.4 P 0.6 (Mg-Ti) 0.2 S 4.4 Cl 0.6 F 1.0 , marked as F1.0. The obtained electrolyte was poured into the solid-state battery mold and pressed into a sheet at a pressure of 350MPa. The cut Li foils were placed on both sides. The current density increment for each cycle was 0.05mAcm-2 The symmetrical battery constant current charge and discharge test was carried out at 28°C. The critical current density of the electrolyte was 1.15 mA cm -2 .

[0056] Example 2

[0057] LiCl, Li2S, P2S5, MgF2, and TiF3 with a molar ratio of 1.28:2.03:0.43:0.05:0.05 were placed in a ball mill, and pre-milled at 100 rpm for 1h, ball milled at 300 rpm for 2h, and ball milled at 400 rpm for 20h to obtain an amorphous phase mixture of argyrodite-type solid electrolyte. The blank was cold-pressed to obtain a blank, placed in a quartz tube, and heated to 450°C at room temperature for 12h. The temperature dropped to room temperature to obtain a ceramic phase sulfide solid electrolyte Li 5.65 P 0.90 (Mg-Ti) 0.05 S 4.4 Cl 1.35 F 0.25 , marked as F0.25. The obtained electrolyte was poured into the solid-state battery mold and pressed into a sheet at a pressure of 350 MPa. The cut Li foils were placed on both sides. The current density increment for each cycle was 0.05 mA cm -2 The symmetrical battery constant current charge and discharge test was carried out at 28°C. The critical current density of the electrolyte was 0.32 mA cm -2 .

[0058] Example 3

[0059] LiCl, Li2S, P2S5, MgF2, and TiF3 with a molar ratio of 1.05:2.29:0.38:0.10:0.10 were placed in a ball mill, and pre-milled at 100 rpm for 1h, ball milled at 300 rpm for 2h, and ball milled at 500 rpm for 20h to obtain an amorphous phase mixture of argyrodite-type solid electrolyte. The blank was cold-pressed to obtain a blank, placed in a quartz tube, and heated to 450°C at room temperature for 12h. The temperature dropped to room temperature to obtain a ceramic phase sulfide solid electrolyte Li 5.9 P 0.8 (Mg-Ti) 0.1 S 4.4 Cl 1.1 F 0.5 , marked as F0.5. The obtained electrolyte was poured into the solid-state battery mold and pressed into a sheet at a pressure of 300 MPa. The cut Li foils were placed on both sides. The current density increment for each cycle was 0.05 mA cm -2 The symmetrical battery constant current charge and discharge test was carried out at 28°C. The critical current density of the electrolyte was 0.34 mA cm -2 .

[0060] Example 4

[0061] LiCl, Li2S, P2S5, MgF2, and TiF3 with a molar ratio of 0.82:2.54:0.34:0.14:0.14 were placed in a ball mill, and pre-milled at 100 rpm for 1h, ball milled at 300 rpm for 2h, and ball milled at 400 rpm for 20h to obtain an amorphous phase mixture of argyrodite-type solid electrolyte. The blank was cold-pressed to obtain a blank, placed in a quartz tube, and heated to 450°C at room temperature for 12h. The temperature dropped to room temperature to obtain a ceramic phase sulfide solid electrolyte Li 6.15 P 0.7 (Mg-Ti) 0.15 S 4.4 Cl 0.85 F 0.75 , marked as F0.75. The obtained electrolyte was poured into the solid-state battery mold and pressed into a sheet at a pressure of 350 MPa. The cut Li foils were placed on both sides. The current density increment for each cycle was 0.05 mA cm -2 The symmetrical battery constant current charge and discharge test was carried out at 28°C. The critical current density of the electrolyte was 4.38 mA cm -2 .

[0062] Example 5

[0063] LiCl, Li2S, P2S5, MgF2, and TiF3 with a molar ratio of 0.96:2.39:0.36:0.11:0.11 were placed in a ball mill, and pre-milled at 100 rpm for 1h, ball milled at 300 rpm for 2h, and ball milled at 400 rpm for 20h to obtain an amorphous phase mixture of argyrodite-type solid electrolytes. The blanks were cold-pressed to obtain a blank, placed in a quartz tube, and heated to 450°C at room temperature for 12h. The temperature was lowered to room temperature to obtain a ceramic phase sulfide solid electrolyte Li 6.0 P 0.76 (Mg-Ti) 0.12 S 4.4 Cl 1.0 F 0.6 , marked as F0.60. The obtained electrolyte was poured into the solid-state battery mold and pressed into a tablet at a pressure of 350MPa. The measured X-ray diffraction pattern is shown in the attached figure. Figure 2 shown.

[0064] Example 6

[0065] LiCl, Li2S, P2S5, MgF2, and TiF3 with a molar ratio of 0.77:2.59:0.33:0.15:0.15 were placed in a ball mill, and pre-milled at 100 rpm for 1h, 300 rpm for 2h, and 400 rpm for 20h to obtain an amorphous phase mixture of argyrodite-type solid electrolyte. The blank was cold-pressed to obtain a blank, placed in a quartz tube, and heated to 450°C for 12h at room temperature. The temperature dropped to room temperature to obtain a ceramic phase sulfide solid electrolyte Li 6.2 P 0.68 (Mg-Ti) 0.16 S 4.4 Cl 0.8 F 0.8 , marked as F0.80. The obtained electrolyte was poured into the solid-state battery mold and pressed into a tablet at a pressure of 350MPa. The measured X-ray diffraction pattern is shown in the attached figure. Figure 2 shown.

[0066] Test Example 1

[0067] Argentum-type solid electrolyte sheets and solid electrolyte LPSCl of Examples 1 to 6 1.6 The photo was taken after the film was immersed in water for 1 minute. Figure 1 As shown, it can be seen that the electrolyte with x>0.12 has excellent wet stability.

[0068] The X-ray diffraction patterns of the argyrodite-type solid electrolytes of Examples 1 to 6 are as follows: Figure 2 As shown in the figure, with the increase of x, the diffraction peak intensity corresponding to 38.7° and 45.0° gradually increases, indicating the precipitation of LiF phase; the diffraction peak intensity corresponding to 52.5° and 53.1° gradually increases, indicating the precipitation of MgF2 and TiF3 phases. This shows that only with appropriate doping amount can pure phase Mg, Ti, F doped LPSCl argyrodite-type solid electrolyte be obtained.

[0069] In Example 1, Li 6.4 P 0.6 (Mg-Ti) 0.2 S 4.4 Cl 0.6 F 1.0 The constant current charge and discharge test curve of the metal lithium symmetric battery assembled as electrolyte is as follows Figure 3 As shown, Li 6.4 P 0.6 (Mg-Ti) 0.2 S 4.4 Cl 0.6 F 1.0The electrolyte was pressed into a battery mold, and cut Li foils were placed on both sides. The Li / / Li symmetric battery constant current charge and discharge test was carried out at 28°C. The current density increment for each cycle was 0.05 mA cm -2 The critical current density of the electrolyte was found to be 1.15 mA cm -2 .

[0070] In Example 1, Li 6.4 P 0.6 (Mg-Ti) 0.2 S 4.4 Cl 0.6 F 1.0 The scanning electron microscope image and energy spectrum of the metal lithium symmetric battery assembled as electrolyte after constant current charge and discharge test are shown in the figure below. Figure 4 As shown in the figure, each element is evenly distributed in the electrolyte, and the F and Cl elements are evenly distributed at the electrolyte / lithium negative electrode interface, forming a dense passivation layer, which improves the lithium metal stability of the electrolyte.

[0071] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A argyrodite-type solid electrolyte, characterized in that: The chemical formula of the argyrodite-type solid electrolyte is Li 5.4+5x P 1-2x (Mg-Ti) x S 4.4 Cl 1.6-5x F 5x ; Among them, 0 <x<0.3。 2. The argyrodite-type solid electrolyte according to claim 1, characterized in that: The ionic conductivity of the argyrodite-type solid electrolyte at 20 to 30° C. is 1 to 4 mS / cm.

3. A method for preparing the argyrodite-type solid electrolyte according to claim 1 or 2, characterized in that: The steps include: The mixed raw materials containing Li2S, P2S5, MgF2, TiF3 and LiCl are ball-milled, roasted and sintered to obtain the argyrodite-type solid electrolyte.

4. The preparation method according to claim 3, characterized in that: In the mixed raw material, the molar ratio of Li2S, P2S5, MgF2, TiF3 and LiCl is calculated based on the molar ratio of each element in the chemical formula of claim 1.

5. The preparation method according to claim 4, characterized in that: The mixed raw material contains 2.03 to 2.80 parts by mass of Li2S, 0.29 to 0.43 parts by mass of P2S5, 0.05 to 0.19 parts by mass of MgF2, 0.05 to 0.19 parts by mass of TiF3, and 0.58 to 1.28 parts by mass of LiCl.

6. The preparation method according to claim 3, characterized in that: The ball milling conditions include: a rotation speed of 100 to 500 r / min, and a ball milling time of 45 to 1200 min.

7. The preparation method according to claim 3, characterized in that: The calcination conditions include: a temperature of 400 to 500° C. and a calcination time of 8 to 12 hours.

8. The preparation method according to claim 7, characterized in that: The step of tableting is also included after the calcination; The tabletting conditions include: a pressure of 10 to 15 MPa.

9. The preparation method according to claim 3, characterized in that: The sintering conditions include: the sintering atmosphere is an inert gas atmosphere, the sintering heating rate is 5-10° C. / min, the sintering temperature is 200-475° C., and the sintering time is 6-12 hours.

10. Use of at least one of the argyrodite-type solid electrolyte according to claim 1 or 2 and the argyrodite-type solid electrolyte prepared according to the preparation method according to any one of claims 3 to 9 as an electrolyte for an all-solid-state lithium-ion battery.

Citation Information

Patent Citations

  • Negative electrode material of lithium ion battery and preparation method thereof

    CN111430676A

  • Lithium-containing argyrodite solid electrolyte with dopant and preparation method of lithium-containing argyrodite solid electrolyte

    CN111430808A

  • Solid electrolyte and preparation method and application thereof

    CN114552021A